Social Movement Activism in the Formation of Ontario New Democratic Party Policy on Abortion, 1982-1984 - Weir, Lorna (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1995)
The conflict within the Ontario New Democratic Party during 1982-1984 on the question of setting party policy in support of the feminist campaign for free-standing abortion clinics is used as a case study to develop three aspects of social movement theory: alliance and conflict systems, radical flank effects, and social movement-political party relations. A previously undocumented radical flank effect is proposed, an inequality effect, arising under conditions when the distinction between radical and dominant sectors of a social movement align with a form of fundamental social inequality. The inequality effect is consequential for creating a distinction in the alliance and conflict systems of the radical and dominant sectors of the movement. It is suggested that the relation of Canadian social democracy to social movements be read as a dynamic tension between constituency representation and brokerage politics.